Large-Range Polymer Optical-Fiber Strain-Gauge Sensor for Elastic Tendons in Wearable Assistive Robots - Cifuentes Garcia, Carlos Andrés; Casas, Jonathan; Leal-Junior, Arnaldo; Díaz, Camilo R.; Frizera, Anselmo; Múnera, Marcela (MDIP, 2019)
This paper presents the development and validation of a polymer optical-fiber strain-gauge sensor based on the light-coupling principle to measure axial deformation of elastic tendons incorporated in soft actuators for wearable assistive robots. An analytical model was proposed and further validated with experiment tests, showing correlation with a coefficient of R = 0.998 between experiment and theoretical data, and reaching a maximum axial displacement range of 15 mm and no significant hysteresis. Furthermore, experiment tests were carried out attaching the validated sensor to the elastic tendon. Results of three experiment tests show the sensor’s capability to measure the tendon’s response under tensile axial stress, finding 20.45% of hysteresis in the material’s response between the stretching and recovery phase. Based on these results, there is evidence of the potential that the fiber-optical strain sensor presents for future applications in the characterization of such tendons and identification of dynamic models that allow the understanding of the material’s response to the development of more efficient interaction-control strategies.

Este artículo presenta el desarrollo y la validación de un sensor de galgas extensométricas de fibra óptica de polímero basado en el principio de acoplamiento de la luz para medir la deformación axial de tendones elásticos incorporados en actuadores blandos para robots de asistencia vestibles. Se propuso un modelo analítico y se validó con pruebas experimentales, mostrando una correlación con un coeficiente de R = 0,998 entre los datos experimentales y los teóricos, y alcanzando un rango de desplazamiento axial máximo de 15 mm y sin histéresis significativa. Además, se realizaron pruebas experimentales fijando el sensor validado al tendón elástico. Los resultados de tres pruebas experimentales muestran la capacidad del sensor para medir la respuesta del tendón bajo tensión axial de tracción, encontrando un 20,45% de histéresis en la respuesta del material entre la fase de estiramiento y la de recuperación. A partir de estos resultados, se evidencia el potencial que presenta el sensor de deformación de fibra óptica para futuras aplicaciones en la caracterización de este tipo de tendones y la identificación de modelos dinámicos que permitan entender la respuesta del material para el desarrollo de estrategias de interacción-control más eficientes.
Keywords: Robótica médica; Robots; Physical human; Robot interaction; Soft robotics; Optical; Fiber strain gauge; Físico humano; Interacción con el robot; Robótica blanda; Óptica; Galga extensométrica de fibra